A Dopamine Pathway Gene Risk Score for Cognitive Recovery Following Traumatic Brain Injury: Methodological Considerations, Preliminary Findings, and Interactions With Sex. Issue 5 (September 2016) - Myrga, John M.; Failla, Michelle D.; Ricker, Joseph H.; Dixon, C. Edward; Conley, Yvette P.; Arenth, Patricia M.; Wagner, Amy K.
Abstract : Objectives: With evidence of sexual dimorphism involving the dopamine (DA)-pathway, and the importance of DA pathways in traumatic brain injury (TBI) recovery, we hypothesized that sex × DA-gene interactions may influence cognition post-TBI. Participants: Adult survivors of severe TBI ( n = 193) consecutively recruited from a level 1 trauma center. Design: Risk allele assignments were made for multiple DA pathway genes using a sex-specific stratified approach. Genetic risk alleles, and their impacts on cognition, were assessed at 6 and 12 months postinjury using unweighted, semiweighted, and weighted gene risk score (GRS) approaches. Main Measures: A cognitive composite score generated from 8 standardized neuropsychological tests targeting multiple cognitive domains. Results: A significant sex × gene interaction was observed at 6 and 12 months for ANKK1 rs1800497 (6M: P = .002, 12M: P = .001) and COMT rs4680 (6M: P = .048; 12M: P = .004); DRD2 rs6279 ( P = .001) and VMAT rs363226 ( P = .043) genotypes were independently associated with cognition at 6 months, with trends for a sex × gene interaction at 12 months. All GRS methods were significant predictors of cognitive performance in multivariable models. Weighted GRS multivariate models captured the greatest variance in cognition: R 2 = 0.344 (6 months); R 2 = 0.441 (12 months), significantly increasing the variance captured from the base prediction models. Conclusions: A sex-specific DA-pathway GRS may be a valuable tool when predicting cognitive recovery post-TBI. Future work should validate these findings and explore how DA-pathway genetics may guide therapeutic intervention.